Role of the ventral portion of intermediate arcopallium in stability of female Bengalese finch song preferences - Coulter, Austin; Prather, Jonathan F. (Frontiers in Psychology, 2025)
The process of decision making is a complex procedure influenced by both external and internal conditions. Songbirds provide an excellent model to investigate the neural mechanisms of decision making, because females rely on acoustic signals called songs as important stimuli in directing their mate choice. Previous experiments by our group and others have implicated secondary auditory brain sites in female evaluation of song quality, including the caudal portions of the nidopallium (NC) and mesopallium (CM). Recent pathway tracing experiments reveal a convergence of those sites onto a third region, the ventral portion of the intermediate arcopallium (AIV), suggesting that AIV may also play an important role in song evaluation and mate choice. Here we combined behavioral testing with lesion inactivation to investigate the role of AIV in song preference of female Bengalese finches (Lonchura striata domestica). Inactivation of AIV was associated with destabilization of rank ordering of song preferences. These data suggest a model in which the convergence of auditory activity in AIV plays an important role in female perception of song quality and production of courtship behaviors. Together with previous results that also demonstrate a role for the auditory areas that converge onto AIV, these findings extend the experimental tractability of this emerging animal model of sensory perception and decision making.